THE EFFECT OF DELAY, STORING WHOLEBLOOD WITH K3EDTA AND NA2EDTA ANTICOAGULANTS ON EXAMINATION RESULTS OF ERYTHROCYTE COUNTS, HEMOGLOBIN LEVELS AND ERYTHROCYTE MORPHOLOGY - Widya Intan Amilya; Andika Aliviameita (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2026)
Background: Sample stability refers to the ability of blood to maintain its quantitative values under specific storage conditions at room temperature (18–25°C) and refrigerated temperature (2–8°C). Objective: To determine the differences in red blood cell count, hemoglobin levels, and erythrocyte morphology using K3EDTA vacutainer and conventional Na2EDTA blood samples under varying temperatures and delay times. Method: This experimental laboratory research used a cross-sectional design involving four male students from the D4 Medical Laboratory Technology Program at Universitas Muhammadiyah Sidoarjo. Samples were stored at room temperature (18–25°C) and cold temperature (2– 8°C) with delays of 0, 12, and 24 hours. Examinations were conducted using a hematology analyzer and blood smear preparations. Should include a concise description of the process by which you conducted your research. Result: Wilcoxon Signed-Rank test results showed no significant differences (p>0.05) in red blood cell count and hemoglobin levels. However, morphological changes were observed, including crenation and hypochromia in K3EDTA samples stored cold for 24 hours, and spherocytes and hyperchromia in Na2EDTA samples stored at room temperature for 12 hours should list the results or outcomes of the work you have done so far. Conclusion: The type of anticoagulant and storage conditions did not significantly affect red blood cell count or hemoglobin levels. However, erythrocyte morphology showed alterations influenced by the type of EDTA, temperature, and storage duration. K₃EDTA was more stable in maintaining erythrocyte morphology compared to Na₂EDTA, particularly at cold temperatures.